T.C. GENÇLİK VE SPOR BAKANLIĞI'NA BAĞLI GENÇLİK MERKEZLERİNDE ÇALIŞAN GENÇLİK LİDERLERİNİN YAŞAM KALİTE DÜZEYLERİNİN İNCELENMESİ - TURHAN, FATİH HARUN (Fırat Üniveristesi, 2018)
Bu araştırmanın amacı; Türkiye Cumhuriyeti Gençlik ve Spor Bakanlığına bağlı 81 il ve ilçelerinde bulunan 278 "Gençlik Merkezi"nde çalışan "Gençlik Liderleri" nin yaşam kalitesi düzeylerini belirlemektir. Araştırma evrenini GSB Gençlik Merkezlerinde çalışan 796 gençlik liderleri oluşmaktadır. Örneklem grubu ise çalışmamamıza gönüllü olarak katılmış 347 gençlik lideri oluşturmuştur. Veri toplama aracı olarak "SF-36 Yaşam Kalitesi Ölçeği" ile kişisel bilgi formundan oluşan anket formu kullanılmıştır. Veriler SPSS 22.0 (Statistical Package for the Social Sciences 22.0) programı ile analiz edilmiştir. Tüm testler için anlamlılık düzeyi (p<.05) olarak alınmıştır. Verilerin analizinde bağımsız gruplar t testi (Independent Samples t-testi) ve "Anova" testi kullanılmıştır. Araştırma kapsamında; kadın gençlik liderlerinin yaşam kalitelerinin erkeklerinkinden yüksek çıkmıştır. 23-26 yaş arası liderlerin genel sağlık düzeylerinin yüksek çıkmış buda bu yaş guruplarının yaşam kalitelerinin yüksek göstermiştir. 1-3 yıl arası çalışan liderlerin yaşam kaliteleri 4 ve üzeri çalışanlardan yüksek çıkmıştır. Hanelerinde ücretli çalışan sayısı 1 olanların yaşam kaliteleri birden fazla olanlardan yüksek çıkmıştır. Bu sonuçlar doğrultusunda gençlerle iç içe çalışan gençlik liderlerinin genel sağlık ve enerji düzeylerinin ortalamanın üzerinde olduğu görülmüştür. Kadın gençlik liderlerinin yaşam kalite düzeyleri erkeklerden fazla olduğu görülmüş, hanelerinde çalışan birey sayısı "1" olanların yaşam kaliteleri 2 ve üzeri olanlardan yüksek çıkmıştır. Çalışma yılı 1-3 olanların 4 ve üzeri olanlardan yüksek yaşam kalitesine sahip olduğu görülmüştür. Anahtar Kelimeler: Gençlik, Liderlik, Gençlik Merkezleri, Gençlik Liderliği, Yaşam Kalitesi

INVESTIGATION OF THE QUAILTY OF LIFE LEVELS OF YOUTH LEADERS WORKING YOUTH CENTERS OF MINISTIRY OF YOUTH AND SPORTS, REPUBLIC OF TURKEY The aim of this study is to determine the levels of quality of life of "Youth Leaders" working in 278 "Youth Centers" in the 81 cities and counties under the administration of the Ministry of Youth and Sports (MOYS), the Republic of Turkey. The population of the study consists of 296 youth leaders working in MOYS Youth Centers. The sample group consists of 347 youth leaders who participated voluntarily in our study. For the data collection tool, the questionnaire consisting of "SF-36 Quality of Life Scale" and a personal information form was adopted. The data were analyzed by using the SPSS 22.0 (Statistical Package for the Social Sciences 22.0) software. The significance level for all the tests was determined to be (p<.05). In the data analysis, independent samples t-tests and "Anova" tests were used. Within the framework of the study, the quality of life levels of female youth leaders were determined to be higher than males. The general health levels of youth leaders between 23-26 years old were determined to be high; indicating that the quality of life levels of this age group was higher. The quality of life levels of leaders working for 1-3 years were determined to be higher compared to those working for 4 or more years. The quality of life levels of those with 1 individual with paid work in the household were determined to be higher than those of with more than one individual with paid work in the household. These results shows that general health and energy levels of youht leaders who works nested youngs were seen above the average . Quality of life levels of female youth leaders have been seen more in males, life quality of houses which has 1 workers is higher than 2 or more.It has been seen that ones who works 1-3 years has more hihger quality of living than 4 or more years. Key Words: Youth, Leadership, Youth Centers, Youth Leadership, Quality of Life
Investigation of the quailty of life levels of youth leaders working youth centers of Ministiry of Youth and Sports, Republic of Turkey
Keywords: Spor